Corporate governance and ESG strategies: The moderating impact of internal audit quality on financial performance in Indonesian companies - Fernandez, Chrysostom; Evandio, Daniel Yanuar; Riantono, Ignatius Edward (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) implementation, greenwashing practices, and corporate governance mechanisms on the financial performance of non-financial firms in Indonesia, an emerging market characterized by evolving sustainability regulations. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) on a sample of firms from the Indonesian non-financial sector, the study assesses ESG disclosure, board structure (including size, independence, and diversity), and the moderating role of internal audit quality. Results show that ESG disclosure and greenwashing do not directly impact financial performance. However, board size, independence, and diversity significantly enhance financial outcomes. Internal audit quality strengthens the positive effects of ESG disclosure, board size, and board independence on firm performance, but does not moderate the impacts of greenwashing or board diversity. This study contributes to the existing literature by providing insights into the nuanced roles of governance and internal audit in shaping ESG outcomes within the context of an emerging economy. Additionally, it supports Indonesia's long-term sustainability vision under the "Golden Indonesia 2045" initiative by emphasizing the importance of internal audit and governance structures in enhancing firm accountability and performance. Our study offers policymakers recommendations on strengthening governance and internal audit to boost ESG and financial performance.